ICT and e-Learning Literacy as an Important Component for the New Competency- based Curriculum Framework in Kosovo - BEQIRI, Edmond (Journal of Research in Educational Sciences; Vol 1 No 1 (2010): JRES Volume I Issue 1(1) Summer 2010, 2010)
This research paper is focused on the role of ICT and e-learning education/literacy as a key component on the Education System of the transition countries. It investigates the importance of ICT and e-learning literacy and their impact on: curriculum development and implementation, Student/Learner-centered teaching/learning, Competency-based approaches, Integrated teaching and learning, Flexibility and mobility, Transparency and accountability. The research explores whether e-learning and ICT can enhance the competency-based curriculum in Kosovo within the new revised Curriculum Framework. The primary research is based on experiences and the level of inclusion of ICT education within the actual 2001 Curriculum Framework (White Discussion Paper), and on the result of intensive and dedicated 12 months work of Kosovo State Curriculum Council (KSCC) that is closely involved in the development of the new 2010 version of the Kosovo Curriculum Framework. The paper also looks at the effects of ICT literacy in all main features of the curriculum stages and their result with Student Personal development of key competencies such as: communication and expression, thinking and learning, Life, work-, and environment-related competencies etc. Finally, the research shows that the ICT and e-learning literacy of teachers needs to change and academics need to embrace new technology since Kosovo society is now reconnected to the most recent developments in science, technology and culture.